2020
DOI: 10.1142/s1793545820500078
|View full text |Cite
|
Sign up to set email alerts
|

Video-rate multimodal multiphoton imaging and three-dimensional characterization of cellular dynamics in wounded skin

Abstract: To date, numerous studies have been performed to elucidate the complex cellular dynamics in skin diseases, but few have attempted to characterize these cellular events under conditions similar to the native environment. To address this challenge, a three-dimensional (3D) multimodal analysis platform was developed for characterizing in vivo cellular dynamics in skin, which was then utilized to process in vivo wound healing data to demonstrate its applicability. Special attention is focused on in vivo biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As antigen‐specific T cells encountering dermal antigen‐presenting cells (APCs) and recognizing antigens in the skin are critical events in T cell‐mediated CHS, [ 28–29 ] we then explored the effect of α ‐melittin‐NPs on antigen recognition between hapten‐specific T cells and APCs in the dermis through intravital imaging of mouse skin. [ 30–32 ] Intravital imaging data in Figure 4I confirmed that α ‐melittin‐NP treatment‐induced hapten‐specific T cells displayed more unrestricted behavior with a higher migration speed (5 µm min −1 ) and lower arrest coefficient (value: 0.5) when compared to PBS treatment. The mean square displacement versus time (MSD‐T) data further confirmed that T cells in the α ‐melittin‐NP‐treated group were prone to more diffuse movement, with a higher confinement ratio than that of T cells in the PBS‐treated control group (Figure 4J–M).…”
Section: Resultsmentioning
confidence: 75%
“…As antigen‐specific T cells encountering dermal antigen‐presenting cells (APCs) and recognizing antigens in the skin are critical events in T cell‐mediated CHS, [ 28–29 ] we then explored the effect of α ‐melittin‐NPs on antigen recognition between hapten‐specific T cells and APCs in the dermis through intravital imaging of mouse skin. [ 30–32 ] Intravital imaging data in Figure 4I confirmed that α ‐melittin‐NP treatment‐induced hapten‐specific T cells displayed more unrestricted behavior with a higher migration speed (5 µm min −1 ) and lower arrest coefficient (value: 0.5) when compared to PBS treatment. The mean square displacement versus time (MSD‐T) data further confirmed that T cells in the α ‐melittin‐NP‐treated group were prone to more diffuse movement, with a higher confinement ratio than that of T cells in the PBS‐treated control group (Figure 4J–M).…”
Section: Resultsmentioning
confidence: 75%
“…The feasibility and the advantages of the currently available CE-certified medical MPT devices and further two-photon skin imaging microscopes for characterizing the human skin in vivo both in medical and cosmetic fields have been largely demonstrated in the past years [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Its clinical applications include the early detection of malignant melanoma and non-melanoma skin cancer as well as inflammation deceases.…”
Section: Introductionmentioning
confidence: 99%